Programa Institucional de Bolsas de Iniciação à Docência (PIBID): contribuições na formação de bolsistas licenciandos em Química - BEZERRA, Ana Carolina Balbino (2017)
The research deals with the Institutional Program of Initiatives for Teaching (PIBID), with emphasis on its conception in the normative basis and its meanings, in the articulation of specific / pedagogical knowledge and in the relations undergraduate / basic education, and theory and practice in the process of teacher training in an institutional experience, seizing contributions and limits. This work is linked to the research line entitled "State and Educational Management" and to the research group "Basic and Higher Education Policy" of the Graduate Program in Education, Federal University of Maranhão. In the methodological course, a bibliographic, documentary and empirical descriptive and analytical study was carried out. Among the authors referenced are: Canan, Garnica, Saviani, Tanuri, Lima, Silva, Gomes, Tancredi, Pires, Medeiros, Farias, Rocha, Manfredi, Freitas, Nacarato, Fiorentini, Gatti, Candau, Manrique, Furkotter, Morelatti, Vásquez, Tardif, Zeichner, Fagundes, Santos, among others. In the exposition of the dissertation text, besides the introduction and conclusion, three sessions were developed. In the introduction we present the theme, the thematic clipping, the research problem, the objectives, the methodological design of the research and the synthesis of the form of exposition of the text. In the second session, we discuss the policies of teacher education for basic education in Brazil, valuing the advances of the normative base from a perspective of what education is right. In the third session, the focus of discussion will be the PIBID, with an emphasis on its historical origin, program design and development. And, in the fourth session, the PIBID is located in UFMA and the participation of the degree in Chemistry and its meanings in teacher training is analyzed. The results of our study demonstrated the potential of PIBID as a transformative program in relation to the contributions in the formation of students in the undergraduate course analyzed. However, despite the transformation that the program brings, it does not reach the totality of the graduates and emphasizes the importance, as well as the necessity of a national policy of valorization of the teachers, since this is configured as a transitional program.